Multiscale characterization of Solito seamount: a unique ecosystem with high conservation value - Jan M. Tapia-Guerra; Javier Sellanes; Erin E. Easton; Yakufu Niyazi; Javier Reyes; Angéline Bertin; Denise J.B. Swanborn; Eduardo A. Flores; Maritza Castro-Contreras; Ignacio Petit; Marco Pérez-González; Carlos F. Gaymer (Progress in Oceanography, 2026)

Biphasic growth modelling in elasmobranchs based on asymmetric and heavy-tailed errors - Javier E. Contreras-Reyes; Rodrigo Wiff; Javier Soto; Carl R. Donovan; Miguel Araya (Environmental Biology of Fishes, 2021)

Endogenous, Climate, and Fishing Influences on the Population Dynamics of Small Pelagic Fish in the Southern Humboldt Current Ecosystem - T. Mariella Canales; Mauricio Lima; Rodrigo Wiff; Javier E. Contreras-Reyes; Ursula Cifuentes; José Montero (Frontiers in Marine Science, 2020)

Sampling Procedure for Establishing Criteria for Sea Urchin (Loxechinus albus) Proportion under the Legal Minimum Length of landings - Gustavo Di Giorgi; Marvin Querales; Javier E. Contreras-Reyes; Danilo Pereira; Carola Hernández-Santoro (Journal of Marine Science and Engineering, 2020)
Sea urchin (Loxechinus albus) is one of the most economically important species in the northeast of Chilean Patagonia, forming part of the highly diverse benthic community. This resource is being harvested under selective fishing pressure, which suppresses growth rates. In response, the National Standards Institute established Regulation 44 as a quality control measure, based on a sampling approach considering the percentage of sea urchin under the minimum legal size (UMLS) through an acceptance sampling plan. In 2019, the Chilean Undersecretary of Fisheries and Aquaculture (SUBPESCA), under Exempt Resolution No. 910, ruled that any vessel that landed 15% with sea urchin of 6.5 cm UMLS of the total catch weight will be sanctioned. In this paper, a sampling design is presented to establish criteria regarding compliance with this provision. The plan provides a statistical methodology for the evaluation of the percentage of UMLS sea urchin, which corroborates and certifies the current legislation that sanctions and fines the capture of sea urchin that does not comply with UMLS values outlined in Regulation 44. Assuming a systematic sampling plan and under assumed UMLS values of 6.0, 6.5, and 7.0 cm, it is determined that 15% of total landings (margin of tolerance) of sea urchin under 6.5 cm is the optimal level. Thus, a correct specification of the UMLS allows protecting the most vulnerable fraction of the population from overexploitation for growth.

Towards Age Determination of Southern King Crab (Lithodes santolla) Off Southern Chile Using Flexible Mixture Modeling - Javier E. Contreras-Reyes; Freddy O. López Quintero; Alejandro A. Yáñez (Journal of Marine Science and Engineering, 2018)
This study addresses the problem of age determination of the southern king crab (Lithodes santolla). Given that recapture is difficult for this species and, thus, age cannot be directly determined with the help of the annual marks on the shell, the von Bertalanffy growth function (vBGF) cannot be used to directly model length-frequency data (LFD). To determine age classes, some researchers have proposed using the MIX algorithm that consists of sampling realization of a finite mixture of normal (FMN) distributions for each LFD. However, normality assumption in age-length data has been questioned in several works related to fish growth analysis. For this study, we considered the biological information of the southern king crab for the period 2007–2015 and localization between 50 ∘ 06 ′ – 53 ∘ 15 ′ S and 76 ∘ 36 ′ – 72 ∘ 18 ′ W. We assumed that LFD could be modelled by the novel class of finite mixture of skew-t (FMST). Assigned age classes were used to estimate the vBGF parameters. The estimated vBGF parameters were L ∞ = 176.756 cm, K = 0.151 year − 1 , t 0 = − 1.678 year for males, and L ∞ = 134.799 cm, K = 0.220 year − 1 , t 0 = − 1.302 year for females. This study concludes that (a) FMST modal decomposition can detect a group of younger individuals at age 2, given that those individuals have LFD with a left heavy-tail and asymmetry; (b) FMST produces a better representation of LFD than the FMN model; (c) males have bigger L ∞ but grow slower than females; and (d) as expected, a high correlation exists among the vBGF estimates.